Method for coating silver on surface of powder

By pretreating and reducing the Ag elemental layer by using Si-H-containing precursors, the problems of poor silver coating uniformity and insufficient binding force on the powder surface in the prior art are solved, and efficient and uniform Ag elemental layer coating effect is achieved.

CN119913494APending Publication Date: 2025-05-02INST OF CHEM CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311420614.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art has problems of poor uniformity and insufficient binding force when the surface of micro-nano-sized powders is coated with silver elemental layers, especially when batch-scale preparation and application to micro-nano-sized powders.

Method used

The Si-H-containing precursor is used as the interface layer construction material, and the powder is pretreated to form a firmly bonded interface layer, and then the Ag elemental layer is reduced and coated. The method includes adding the powder to the Si-H-containing precursor solution for pretreatment, then mixing with the silver plating solution, and reacting under controlled pH and heating conditions to form a uniform Ag single material layer.

Benefits of technology

A single Ag layer structure with uniform surface of powder without exposed bottom defects is achieved, and the bonding force between the Ag layer and the powder surface is significantly improved, ensuring the coating quality and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913494A_ABST
    Figure CN119913494A_ABST
Patent Text Reader

Abstract

The invention discloses a method for coating silver on the surface of powder. The method comprises the following steps: (S1) adding the powder into a solution containing a Si-H precursor for pretreatment to obtain surface-modified powder; and (S2) mixing the Si-H precursor surface modified powder prepared in the step (S1) with a silver plating solution to obtain the powder coated with silver on the surface. According to the method, a Si-H-containing precursor is adopted as an interface layer building material. Si-H bonds in the precursor structure can be converted into Si-OH and Si-O-Si bonds under the action of water and / or oxygen; meanwhile, residual Si-H bonds in the precursor structure have reducibility, and various metal ions and oxidizing substances can be reduced. In addition, chemical bonds can be formed between the precursor and various materials such as metal, oxide, ceramic, glass, polymer and the like, so that the precursor and SiOx formed by conversion of the precursor have excellent adhesive force on different substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional material preparation, and in particular relates to a method for coating the surface of a powder with silver. Background Art

[0002] Silver (Ag) has the characteristics of good conductivity, high reflectivity, and good antioxidant properties. By coating it on the surface of organic or inorganic powders, multifunctional new materials can be prepared. For example, by coating silver on the surface of hollow glass microspheres, a thermal insulation material with excellent electromagnetic shielding performance can be obtained; by coating silver on the surface of magnetic materials, such as carbonyl iron powder and iron oxide powder, the dark color characteristics of conventional magnetic powders can be changed, which is convenient for the later expansion of their applications; by coating silver on the surface of carbon powder, the conductivity of the powder can be further improved and the electromagnetic shielding effect can be given; by compounding silver with copper, the copper can be given antioxidant and chemical corrosion resistance without affecting its conductive properties. The typical silver coating process is the chemical silver plating process. For example, the invention patent CN109402613A discloses a method of forming a single Ag layer on the surface of zinc oxide whiskers using the "silver mirror reaction". In order to realize the interfacial adsorption, reduction and growth of Ag, it is necessary to carry out complex pretreatment of the powder before the silver mirror reaction, including steps such as coarsening, sensitization, activation and degumming, which not only has complicated process steps, but also the formed Ag layer is physically adsorbed with the powder surface, and the interfacial adhesion is weak. In addition, vapor deposition (vacuum sputtering, plasma vapor deposition) is also a common means, and the silver coating on the surface of various materials can be realized by this method. However, this method has limitations in batch scale preparation, and there is a problem of uneven powder coating. Forming a silver coating on the surface of a substrate by electroplating technology is the main method for preparing large-scale silver-plated parts. Invention patent CN 109267124 A discloses a method for forming a composite Ag coating on a graphite surface by electroplating process, but this method has problems of low coating quality and poor uniformity when applied to micro-nano size powders. Summary of the invention

[0003] In order to solve the above technical problems, the present invention aims to provide a universal and convenient method for coating the surface of micro-nano-sized powder with a single Ag layer, which can improve the bonding force between the Ag layer and the powder surface while ensuring that the structure of the single Ag layer is uniform and free of bottom defects.

[0004] The technical solution of the present invention is as follows:

[0005] A method for coating the surface of a powder with silver, comprising:

[0006] (S1) adding the powder into a solution containing a Si-H precursor for pretreatment to obtain a surface-modified powder;

[0007] (S2) Mixing the powder surface-modified by Si-H precursor prepared in step (S1) with a silver plating solution to obtain a powder surface-coated with silver.

[0008] According to an embodiment of the present invention, when there are pollutants such as oil and / or impurities on the surface of the powder, the powder further includes a cleaning step before being added to the solution containing the Si-H precursor. Therefore, the preparation method includes:

[0009] (1) Use alcohol solvent to clean the powder;

[0010] (2) adding the powder cleaned in step (1) into a solution containing a Si-H precursor for pretreatment to obtain a surface-modified powder;

[0011] (3) Mixing the powder surface-modified by Si-H precursor prepared in step (2) with a silver plating solution to obtain a powder surface-coated with silver.

[0012] According to an embodiment of the present invention, the powder in step (1) is an inorganic powder or an organic powder, for example, metal powder, metal oxide powder, non-metal oxide powder, ceramic powder, carbon black powder, polystyrene (PS) spherical powder, polymethacrylate (PMMA) spherical powder.

[0013] According to an embodiment of the present invention, the size of the powder in step (1) is 5 nm to 100 μm; preferably 0.5 μm to 20 μm, for example 1 μm to 10 μm.

[0014] According to an embodiment of the present invention, in step (1), when the powder is selected from carbon black powder, PS ball powder or PMMA ball powder, a step of treating the hydroxyl groups on the surface of the powder is required. The specific method is to pretreat the above powder with a NaOH solution, add the powder to the NaOH solution, heat and stir for a period of time, filter, wash with deionized water, and dry in a vacuum oven;

[0015] The mass of the NaOH solution is 1 to 50 times the mass of the powder, preferably 2 to 10 times;

[0016] The pH of the NaOH solution is 8 to 14, preferably 10 to 13;

[0017] The stirring time is 1 min to 24 h; preferably 30 min to 4 h;

[0018] The heating temperature is 30-100°C, preferably 40-80°C;

[0019] The oven temperature is 40-120°C, preferably 60-80°C;

[0020] According to an embodiment of the present invention, in step (1), the alcohol solvent is selected from methanol, ethanol, isopropanol, etc.

[0021] According to an embodiment of the present invention, the step (1) comprises: adding the powder to be treated into ethanol, stirring, filtering, and drying.

[0022] According to the embodiment of the present invention, the detailed operation of step (1) is: adding the powder to be treated into a beaker, adding an appropriate amount of ethanol, mixing the ethanol and the powder for a period of time by mechanical stirring, and then transferring the powder to an oven for drying after filtering to obtain clean powder. This step is to use ethanol to clean the powder to remove pollutants such as oil or impurities on the surface of the powder.

[0023] According to an embodiment of the present invention, in step (1), the added mass of the alcohol solvent is 0.5 to 100 times the mass of the powder, preferably 2 to 10 times;

[0024] According to an embodiment of the present invention, in step (1), the stirring time is 1 min to 24 h; preferably 30 min to 4 h;

[0025] According to an embodiment of the present invention, in step (1), the oven treatment temperature is 30°C to 200°C; preferably 80°C to 120°C.

[0026] According to an embodiment of the present invention, step (2) comprises: dispersing the powder prepared in step (1) in a solution containing a Si-H precursor (eg, inorganic polysilazane), and heating the solution under a nitrogen atmosphere for reaction.

[0027] According to the embodiment of the present invention, the detailed operation of step (2) is: dispersing the powder in a solution containing a Si-H precursor, heating the reaction under the protection of an inert gas (such as a nitrogen atmosphere), mechanically stirring for a period of time, so that the precursor is grafted onto the surface of the powder, and then filtering and washing the powder, transferring it to a vacuum oven for drying, and obtaining a powder containing a surface modified by the Si-H precursor;

[0028] According to an embodiment of the present invention, the Si-H-containing precursor is inorganic polysilazane (PHPS), organic polysilazane (108), hydrogen-containing polycarbosilane (HPCS), hydrogen-containing polysiloxane (PHMS) and hydrogen-containing siloxane.

[0029] According to an embodiment of the present invention, in step (2), the viscosity of the precursor solution is 2 cP to 50 cP;

[0030] According to an embodiment of the present invention, in step (2), the solvent of the precursor solution can be selected from at least one of hydrocarbon solvents, halogenated hydrocarbon solvents, ether solvents, ketone solvents, aromatic solvents, and ester solvents; specifically, the solvent is selected from at least one of n-hexane, heptane, octane, decane, petroleum ether, dichloromethane, chloroform, dichloroethylene, ethyl ether, butyl ether, acetone, cyclohexanone, methyl ethyl ketone, isophorone, toluene, o-xylene, p-xylene, m-xylene, chlorobenzene, ethyl acetate, butyl butyrate, amyl acetate, and octyl acetate.

[0031] According to an embodiment of the present invention, in step (2), the concentration of the precursor solution is 0.01 wt% to 10 wt%, for example, 0.5 wt% to 5 wt%, such as 1 wt% to 4 wt%;

[0032] According to an embodiment of the present invention, in step (2), the ratio of the mass of the precursor solution to the mass of the powder is 0.5:1 to 100:1; preferably 2:1 to 10:1;

[0033] According to an embodiment of the present invention, in step (2), the heating reaction temperature is 35°C to 120°C; preferably 50°C to 100°C;

[0034] According to an embodiment of the present invention, in step (2), the stirring time is 1 min to 24 h; preferably 1 h to 5 h;

[0035] According to an embodiment of the present invention, in step (2), the oven treatment temperature is 30°C to 200°C; preferably 80°C to 120°C.

[0036] According to an embodiment of the present invention, in step (2), the pH of the system is 8-14, preferably 9-12.

[0037] According to an embodiment of the present invention, step (3) comprises: adding the powder prepared in step (2) and surface-modified by Si-H precursor into a silver plating solution for heating reaction.

[0038] According to the embodiment of the present invention, the detailed operation of step (3) is as follows: adding the powder modified by the Si-H precursor prepared in step (2) into a beaker, then adding a certain amount of silver plating solution, heating for reaction, and mechanically stirring and mixing for a period of time; during this process, the Si-H of the Si-H precursor is hydrolyzed and converted into Si-O-Si and Si-OH bonds, and the residual Si-H bonds can reduce the Ag in the silver plating solution. + Generate a single layer or several layers of Ag single substance layer;

[0039] According to an embodiment of the present invention, in step (3), the silver plating solution is a silver ammonia solution, and its preparation method is: add a certain amount of AgNO3 into deionized water and fully dissolve it, then add concentrated ammonia water while stirring until the color of the solution changes from brown to dark brown, and then stops adding when it just becomes colorless;

[0040] According to an embodiment of the present invention, in step (3), the ratio of the mass of the silver plating solution to the mass of the powder is 0.5:1 to 100:1; preferably 5:1 to 50:1;

[0041] According to an embodiment of the present invention, in step (3), the pH value of the silver plating solution is 8 to 14; preferably 9 to 13;

[0042] According to an embodiment of the present invention, in step (3), the mass concentration of the AgNO3 solution is 1wt% to 30wt%; preferably 5wt% to 20wt%;

[0043] According to an embodiment of the present invention, in step (3), the concentration of the aqueous ammonia is 5wt% to 26wt%; preferably 15wt% to 26wt%;

[0044] According to an embodiment of the present invention, in step (3), the heating reaction temperature is 35°C to 120°C; preferably 40°C to 80°C;

[0045] According to an embodiment of the present invention, in step (3), the stirring time is 1 min to 24 h; preferably 30 min to 4 h.

[0046] According to an embodiment of the present invention, the method further comprises step (4), wherein the step (4) is to add a reducing agent to the mixed solution treated in step (3), and heat the mixture for reaction. At the same time, mechanical stirring is used to mix the mixture evenly, so that the Ag atoms generated by reduction continue to grow on the surface of the Ag layer generated in step (3), until Ag + Exhausted.

[0047] According to the embodiment of the present invention, the detailed operation of step (4) is: continuously adding a certain amount of reducing agent to the mixed solution treated in step (3) to react, and mechanically stirring and mixing to make the Ag atoms generated by reduction continue to grow on the surface of the Ag layer generated in step (3) until Ag + Here, the Ag layer formed in step (3) serves as a nucleation-growth site for Ag atoms, gradually forming a thicker Ag layer on the surface of the powder.

[0048] According to an embodiment of the present invention, in step (4), the reducing agent includes but is not limited to one or a mixture of glucose solution, sodium tartrate solution, and formaldehyde solution;

[0049] According to an embodiment of the present invention, in step (4), the concentration of the reducing agent is 1 wt% to 50 wt%; preferably 5 wt% to 20 wt%;

[0050] According to an embodiment of the present invention, in step (4), the reducing agent droplet acceleration rate is 0.1 mL / s to 100 mL / s; preferably 1 mL / s to 10 mL / s;

[0051] According to an embodiment of the present invention, in step (4), the mass ratio of the silver plating solution to the reducing agent is 1:1 to 1:100; preferably 2 to 10;

[0052] According to an embodiment of the present invention, in step (4), the reaction temperature is 20°C to 80°C; preferably 40°C to 70°C;

[0053] According to an embodiment of the present invention, in step (4), the stirring time is 1 min to 24 h, preferably 2 h to 6 h.

[0054] According to an embodiment of the present invention, the method further comprises a step (5); the step (5) is a separation and drying step.

[0055] According to an embodiment of the present invention, the detailed operation of step (5) is: obtaining the Ag layer-coated powder by filtration, washing the filtered powder multiple times with deionized water to remove impurities, and then transferring the powder to an oven for drying.

[0056] According to an embodiment of the present invention, in the step (5), the oven treatment temperature is 40 to 120°C.

[0057] The present invention also provides powder prepared by the above method.

[0058] The present invention also provides the use of the powder prepared by the above method in the fields of special coatings, wave absorbing materials, electromagnetic shielding, conductive slurry and high dielectric materials.

[0059] Beneficial Effects

[0060] The present invention uses a Si-H-containing precursor as an interface layer construction material. The Si-H bonds in the precursor structure can be converted into Si-OH and Si-O-Si bonds under the action of water and / or oxygen; at the same time, the residual Si-H bonds in the precursor structure are reducible and can reduce a variety of metal ions and oxidizing substances. In addition, the precursor can form chemical bonds with a variety of materials such as metals, oxides, ceramics, glass, polymers, etc., so that the precursor and the SiO x Excellent adhesion on different substrates.

[0061] The present invention utilizes the above-mentioned characteristics of the precursor and uses it as an interface agent to pre-treat the powder, and then performs reduction coating on the Ag single layer. Specifically:

[0062] (1) The method of the present application forms a firmly bonded interface layer on the surface of the powder by treating the Si-H-containing precursor, which is beneficial to improving the bonding strength between the powder and the silver single layer; part of the Si-H in the Si-H-containing precursor is hydrolyzed and converted into Si-O-Si and Si-OH bonds, which effectively improves the bonding force between the Ag atoms and the powder;

[0063] (2) The Si-H bonds in the Si-H-containing precursor are reductive. The degree of conversion of the Si-H-containing precursor can be controlled by controlling the pH of the system. The residual Si-H bonds in the structure can reduce the Ag + Reduced to Ag atoms and attached to the surface of the powder. After this step, the powder surface is finally coated with a single layer or several layers of Ag atoms, providing sites for further growth of the Ag layer, inhibiting the self-nucleation reaction of Ag atoms, and effectively improving the quality and efficiency of Ag coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 These are scanning electron microscope images of the powder in Example 1 before and after being coated with Ag (Figure a is before coating, and Figure b is after coating).

[0065] Figure 2 These are scanning electron microscope images of the powder in Example 2 before and after being coated with Ag (Figure a is before coating, and Figure b is after coating).

[0066] Figure 3 These are scanning electron microscope images of the powder in Example 3 before and after being coated with Ag (Figure a is before coating, and Figure b is after coating).

[0067] Figure 4 These are scanning electron microscope images of the powder in Example 4 before and after being coated with Ag (Figure a is before coating, and Figure b is after coating).

[0068] Figure 5 These are scanning electron microscope images of the powder in Example 5 before and after being coated with Ag (Figure a is before coating, and Figure b is after coating).

[0069] Figure 6 These are scanning electron microscope images of the powder in Example 6 before and after being coated with Ag (Figure a is before coating, and Figure b is after coating).

[0070] Figure 7 These are scanning electron microscope images of the powders in Examples 7 to 10 after being coated with Ag (Figure a is Example 7, Figure b is Example 8, Figure c is Example 9, and Figure d is Example 10).

[0071] Figure 8These are scanning electron microscope images of the powder in Comparative Example 1 before and after being coated with Ag (Figure a is before coating, and Figure b is after coating).

[0072] Fig. 9 The scanning electron microscope images after the silver-plated layer bonding test (Figure a is the powder of comparative example 1 coated with an Ag layer and dispersed by a three-roller machine, and Figure b is the powder of embodiment 1 coated with an Ag layer and dispersed by a double-roller machine).

[0073] Fig.10 This is a schematic diagram of the process of using PHPS to silver-coat powder in this application. DETAILED DESCRIPTION

[0074] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0075] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0076] The powders used in the following examples were all purchased commercially.

[0077] Example 1

[0078] (1) 10 g of black carbonyl iron powder (particle size 1-10 μm) was added to a beaker, followed by 50 ml of ethanol, and the mixture was dispersed by mechanical stirring for 2 h at a speed of 300 rpm, filtered, and the powder was transferred to an oven and dried at 80°C to obtain a clean powder;

[0079] (2) Add the cleaned powder in step (1) to a single-mouth bottle, and then add a p-xylene solution with PHPS as a precursor, the solution concentration is 0.5wt%, the number average molecular weight of PHPS is 1500, the solution viscosity is 5cP, and the pH is 10.5. Under nitrogen protection, heat the reaction at 50°C, stir for 2h, and rotate at 300rpm; then filter and transfer to a vacuum oven for drying at 80°C for 2h to obtain PHPS surface-modified powder;

[0080] (3) The dried powder was added to a beaker, and then 100 ml of a 5% silver plating solution was added. The mixture was heated at 60°C for reaction. A NaOH solution with a pH of 10 was added dropwise to adjust the solution pH to 8 to control the degree of conversion of Si-H bonds in PHPS. The mixture was stirred for 1 h at a speed of 300 rpm to allow the PHPS on the surface of the powder to undergo a Si-N hydrolysis reaction to generate Si-O-Si and Si-OH bonds, and Si-H bonds to be converted into Si-O-Si and Si-OH bonds by the addition of Ag. + Then Ag+ The Ag atoms are generated by reduction and conversion and attached to the surface of the powder, and finally a powder with a single or several layers of Ag atoms on the surface is obtained;

[0081] (4) 400 ml of reducing agent was added dropwise to the beaker. The reducing agent was a mixed solution of glucose / sodium tartrate (the mass ratio of the two was 5:1 and the total mass concentration was 5%). The dropping rate was 1 ml / s. The reaction was stirred at 40°C for 2 h. The stirring rate was 300 rpm. The Ag atoms reduced in the system used the Ag layer formed in step (3) as the nucleation-growth site and gradually grew a thicker Ag layer on the surface of the powder.

[0082] (5) After filtering, the powder was transferred to a vacuum oven at 80°C for 2 h to obtain a light-colored powder;

[0083] (6) Scanning electron microscopy (SEM) revealed that ( Figure 1 ), a continuous and uniform Ag single layer was formed on the surface of the powder.

[0084] Example 2

[0085] The difference from Example 1 is that in step (1), 10 g of black ferroferric oxide powder (particle size 0.5-5 μm) is taken. The scanning electron microscopy test results of the powder before and after silver coating are as follows: Figure 2 shown.

[0086] Example 3

[0087] The difference from Example 1 is that in step (1), 10 g of carbon black powder (particle size 1-10 μm) is taken, washed with alcohol, transferred to a beaker, then 100 ml of NaOH solution (pH=12) is added, heated at 50°C, mechanically stirred for 2 h, the speed is 300 rpm, filtered, and the powder is transferred to an oven at 80°C for drying to obtain a surface hydroxylated powder. The scanning electron microscopy test results of the powder before and after silver coating are shown in FIG. Figure 3 shown.

[0088] Example 4

[0089] The difference from Example 1 is that in step (1), 10 g of gray aluminum powder (particle size 0.1-2 μm) is taken. The scanning electron microscopy test results of the powder before and after silver coating are as follows: Figure 4 shown.

[0090] Example 5

[0091] The difference from Example 1 is that in step (1), 10 g of silicon oxide (SiO x ) powder (particle size 0.5-5 μm). The SEM test results of the powder before and after silver coating are as follows Figure 5 shown.

[0092] Example 6

[0093] The difference from Example 3 is that in step (1), 10 g of polystyrene (PS) micro-nanospheres (particle size 0.5-10 μm) are taken. The scanning electron microscopy test results of the powder before and after silver coating are as follows: Figure 6 shown.

[0094] Example 7

[0095] The difference from Example 1 is that in step (1), the precursor solution is adjusted to a p-xylene solution of HPCS, the solution concentration is 0.6wt%, the number average molecular weight of HPCS is 1200, and the solution viscosity is 4cP. The scanning electron microscopy test results of the powder after silver coating are as follows: Figure 7 As shown in a.

[0096] Example 8

[0097] The difference from Example 1 is that in step (1), the precursor solution is adjusted to a p-xylene solution of the organopolysilazane (108), the solution concentration is 0.4 wt %, the number average molecular weight of the organopolysilazane is 800, and the solution viscosity is 5 cP. The scanning electron microscopy test results of the powder after silver coating are as follows: Figure 7 As shown in b.

[0098] Example 9

[0099] The difference from Example 1 is that in step (1), the precursor solution is adjusted to a tetrahydrofuran solution of PHMS, the solution concentration is 0.5wt%, the number average molecular weight of PHMS is 1000, and the solution viscosity is 5cP. The scanning electron microscopy test results of the powder after silver coating are as follows: Figure 7 As shown in c.

[0100] Example 10

[0101] The difference from Example 1 is that in step (1), the precursor solution is adjusted to a tetrahydrofuran solution of tetramethyldisiloxane, and the solution concentration is 0.5 wt %. The scanning electron microscopy test results of the powder coated with silver are as follows: Figure 7 As shown in d.

[0102] Comparative Example 1

[0103] The difference from Example 1 is that the cleaned powder is directly subjected to chemical silver plating without PHPS treatment. The scanning electron microscopy test results of the powder before and after silver coating are as follows: Figure 8 shown.

[0104] The specific preparation process is as follows:

[0105] (1) 10 g of black carbonyl iron powder (particle size 1-5 μm) was added to a beaker, followed by 50 ml of ethanol, and the mixture was stirred for 2 h using a mechanical stirrer at a speed of 300 rpm, filtered, and the powder was transferred to a vacuum oven at 80°C for drying to obtain a clean powder;

[0106] (2) Add the dried powder to a beaker, then add 100 ml of a 5% silver plating solution, heat at 60° C. and stir for 1 h at a speed of 300 rpm to evenly disperse the powder;

[0107] (3) Add 400 ml of a 5% glucose / sodium tartrate mixed solution (mass ratio of 5:1, total mass concentration of 5%) as a reducing agent by dropwise addition at a dropwise acceleration rate of 1 ml / s, and stir the reaction for 2 h at a stirring rate of 300 rpm;

[0108] (4) After filtering, the powder was transferred to an oven at 80°C for drying for 2 h. The final coated powder was dark in color.

[0109] Test Example 1 Silver coating effect test

[0110] The prepared powders were characterized by SEM. The results showed that the Ag single substance distribution on the surface of the powder of Comparative Example 1 without PHPS treatment was uneven, and the Ag single substance layer on the surface of some powders was discontinuous and scattered on the powder surface in the form of islands ( Figure 8 ).

[0111] Silver coating adhesion test:

[0112] (1) Take 1g of the coated powders of Comparative Example 1 and Example 1, add them into 10g of epoxy resin, and then use a double-roller dispersing device to fully mix the powders and the epoxy resin matrix for 30 minutes. In this process, the powders will be subjected to external forces such as extrusion and friction. If the Ag layer is not firmly bonded to the powder, the Ag layer will be damaged, delaminated, or fall off.

[0113] (2) washing the epoxy resin in the mixture with toluene, then filtering, washing and drying at 80° C.;

[0114] Through SEM characterization, it was found that the Ag layer on the surface of the powder of Comparative Example 1, which was directly coated with Ag without PHPS treatment, showed obvious peeling, stratification and shedding after double-roller dispersion; while the Ag layer of the powder of Example 1, which was treated with PHPS and then coated with Ag, did not show damage or shedding after the external force was applied, but the surface became smooth. This is because the external force caused the surface of the Ag layer to deform ( Fig. 9 ). The above results show that the PHPS interface layer can significantly improve the bonding force between the Ag layer and the powder.

[0115] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for coating the surface of a powder with silver, characterized in that: include: (S1) adding the powder into a solution containing a Si-H precursor for pretreatment to obtain a surface-modified powder; (S2) Mixing the powder surface-modified by Si-H precursor prepared in step (S1) with a silver plating solution to obtain a powder surface-coated with silver.

2. The method according to claim 1, characterized in that When there are oil stains and / or impurities on the surface of the powder, the powder further includes a cleaning step before being added to the solution containing the Si-H precursor; in this case, the preparation method includes: (1) Use alcohol solvent to clean the powder; (2) adding the powder cleaned in step (1) into a solution containing a Si-H precursor for pretreatment to obtain a surface-modified powder; (3) Mixing the powder surface-modified by Si-H precursor prepared in step (2) with a silver plating solution to obtain a powder surface-coated with silver.

3. The method according to claim 2, characterized in that The powder in step (1) is an inorganic powder or an organic powder, for example, a metal powder, a metal oxide powder, a non-metal oxide powder, a ceramic powder, a carbon black powder, a polystyrene (PS) spherical powder, or a polymethacrylate (PMMA) spherical powder; Preferably, the size of the powder in step (1) is 5 nm to 100 μm.

4. The method according to claim 2 or 3, characterized in that: In step (1), when the powder is selected from carbon black powder, PS ball powder or PMMA ball powder, a step of treating hydroxyl groups on the surface of the powder is required; the specific method is to add the above powder to a NaOH solution and heat and stir.

5. The method according to claim 4, characterized in that The mass of the NaOH solution is 1 to 50 times the mass of the powder; Preferably, the pH of the NaOH solution is 8 to 14; Preferably, the heating temperature is 30 to 100°C; Preferably, the heating treatment time is 1 min-24 h.

6. The method according to claim 2, characterized in that In step (1), the alcohol solvent is selected from methanol, ethanol, and isopropanol; Preferably, in step (1), the amount of the alcohol solvent added is 0.5 to 100 times the mass of the powder; Preferably, in step (1), the stirring time is 1 min to 24 h.

7. The method according to claim 2, characterized in that Step (2) comprises: dispersing the powder prepared in step (1) in a Si-H precursor solution, and heating the solution under the protection of an inert atmosphere for reaction; Preferably, the Si-H-containing precursor is an inorganic polysilazane, an organic polysilazane, a hydrogen-containing polycarbosilane, a hydrogen-containing polysiloxane, and a hydrogen-containing siloxane; Preferably, in step (2), the viscosity of the precursor solution is 2 cP to 50 cP; Preferably, in step (2), the solvent of the precursor solution is selected from at least one of hydrocarbon solvents, halogenated hydrocarbon solvents, ether solvents, ketone solvents, aromatic solvents, and ester solvents; Preferably, in step (2), the concentration of the precursor solution is 0.1wt% to 10wt%; Preferably, in step (2), the ratio of the mass of the precursor solution to the mass of the powder is 0.5:1 to 100:1; Preferably, in step (2), the heating reaction temperature is 35°C to 120°C; Preferably, in step (2), the pH of the system is 8-14.

8. The method according to claim 2, characterized in that: Step (3) comprises: adding the powder prepared in step (2) and surface-modified by Si-H precursor into a silver plating solution and heating for reaction; Preferably, in step (3), the silver plating solution is a silver ammonia solution, and the preparation method thereof is: adding a certain amount of AgNO3 into deionized water and fully dissolving it, then adding concentrated ammonia water while stirring until the color of the solution changes from brown to dark brown, and then stops adding when it just becomes colorless; Preferably, in step (3), the ratio of the mass of the silver plating solution to the mass of the powder is 0.5:1 to 100:1; Preferably, in step (3), the pH value of the silver plating solution is 8 to 14; Preferably, in step (3), the mass concentration of the AgNO3 solution is 1wt% to 30wt%; Preferably, in step (3), the concentration of the aqueous ammonia is 5wt% to 26wt%; Preferably, in step (3), the heating reaction temperature is 35°C to 120°C. Preferably, the method further comprises step (4), wherein step (4) is to add a reducing agent to the mixed solution treated in step (3) for reaction. Preferably, in step (4), the reducing agent is selected from one or a mixture of glucose solution, sodium tartrate solution, and formaldehyde solution. Preferably, in step (4), the reaction temperature is 20°C to 80°C.

9. The powder prepared by the method according to any one of claims 1 to 8.

10. Use of the powder prepared by the method according to any one of claims 1 to 8 in the fields of special coatings, wave absorbing materials, electromagnetic shielding, conductive slurries and high dielectric materials.

Citation Information

Patent Citations

  • Silver coated graphite composite coating layer and preparation method thereof

    CN109267124A

  • Method for coating surface of matrix with silver and silvered tetrapod-shapedzinc oxidewhisker prepared by same

    CN109402613A